2018
DOI: 10.15282/jmes.12.3.2018.2.0333
|View full text |Cite
|
Sign up to set email alerts
|

Processing and properties of high density polyethylene/date palm fiber composites prepared by a laboratory mixing extruder

Abstract: In this work, "green" composites made from High Density Polyethylene (HDPE) and natural fiber based date palm fiber have been prepared and studied. The effects of different loadings of date palm fibers (DPF) on the morphological, thermal and melt rheological properties of the composites have been investigated. Morphological investigation showed that the fibers were evenly dispersed in HDPE matrix at all DPF loadings. Additionally, the results of differential scanning calorimetry (DSC) analysis revealed that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…It has been a part of man's technology since the first ancient builder used straw to reinforce mud bricks [4]. Composite properties are however dependent on the characteristics of polymer matrix, properties, content and dispersion of the filler and the interface compatibility, of which influence was studied in the past [5][6][7][8][9]. However, finding some alternative sources of natural fibres from post-consumer waste and how they will be processed with the recycled solid waste plastic for the mass production of new products is a new concept, driven by the circular economy business model.…”
Section: Mechanical and Thermal Properties Of Recycled Mixed Waste Pomentioning
confidence: 99%
See 1 more Smart Citation
“…It has been a part of man's technology since the first ancient builder used straw to reinforce mud bricks [4]. Composite properties are however dependent on the characteristics of polymer matrix, properties, content and dispersion of the filler and the interface compatibility, of which influence was studied in the past [5][6][7][8][9]. However, finding some alternative sources of natural fibres from post-consumer waste and how they will be processed with the recycled solid waste plastic for the mass production of new products is a new concept, driven by the circular economy business model.…”
Section: Mechanical and Thermal Properties Of Recycled Mixed Waste Pomentioning
confidence: 99%
“…where is the heat fusion of the sample, is the heat of fusion of a 100% crystalline PE = 293 J/g [8] and mass fraction of PE in composites.…”
Section: Characterization Analysesmentioning
confidence: 99%
“…From the differential scanning calorimetry (DSC) analysis results revealed that the addition of the DPF into the HDPE matrix has increased the crystallization temperature. However, the crystallinity index of the composites at all DPF loadings was lower than the neat HDPE, which could be related to the hindered movement of the HDPE molecular chains by the presence of the fibres [15]. The comparison study of using extracted fibre from waste and residue of Malaysian's palm oil (OPF) with Japanese type cedar thinned wood fibre on the tensile and impact properties reinforced PP was investigated.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, natural fibers have been widely studied by experts as industrial materials such as mengkuang fibers, palm fibers, akaa (corypha) fibers, king pineapple leaf fibers, coconut fibers, carica papaya fibers, albizia amara fibers, and juncus effuses L fibers [1][2][3][4][5][6][7][8][9]. This study discusses the treatment of Sago fiber (SF) using acetic acid in liquid smoke from coconut shell which is more eco-friendly than other alkali treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies attempted various treatments on natural fibers including immersion in solutions (NaOH, KMnO4, H2O2, and seawater), heating with turmeric solution, and steaming [2,3,6,[10][11][12][13]. The treatments had altered physical properties of fibers, such as lignin level reduction from coconut husk by immersion in NaOH, cleared and shaped grooves by immersion in KMnO4 and H2O2 [3].…”
Section: Introductionmentioning
confidence: 99%